The role of media and people's perception on electronic cigarette/vape in Malaysia - Draman, Samsul; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Tee, Guat Hiong (Malaysia Medical Association, 2017)
The use of electronic cigarette / vape (ECV) has increased rapidly around the world ever since its introduction into the global market. This study investigated the Malaysian general public's sources of information and their perception on ECV. OBJECTIVES: To explore role of media and people's perception of e-cigarette. Methods: A questionnaire (NECS Questionnaire Survey Form) was designed and validated, and given to 6,000 Malaysians ages 18 and above in 6 different geographical zones in the entire Malaysia. SPSS and STATA were used for data analysis. Results: A total of 4,288 individual responded, representing 19 million of Malaysian population. Majority of them were aged 25-44 years old (44%), completed at least secondary education (69%), of Malay ethnicity (73%), were Muslims (79%), and married (68%). Less than half of the respondents knew about ECV through media. Social media, the internet, and vape shops were the most frequently used platform to promote ECV. About onefifth of the respondents received information on the danger of using ECV from television. More than half of the respondents thought a lot about the health risks on using ECV after obtaining information on its health effects. Majority of the respondents disagreed that ECV is more effective than medications in quitting smoking, ECV helps people maintain cigarette abstinence, and ECV is less harmful to health.